Radiological evaluation of pancreatic cancer: What is the significance of arterial encasement >180° after neoadjuvant treatment?. Issue 137 (April 2021) - Mayer, P.; Giannakis, A.; Klauß, M.; Gaida, M.M.; Bergmann, F.; Kauczor, H.U.; Feisst, M.; Hackert, T.; Loos, M.
Abstract: Purpose: This study aimed to evaluate contrast-enhanced computed tomography (CE-CT) features for prediction of arterial tumor invasion in pancreatic cancer (PDAC) patients in the event of arterial encasement >180° after neoadjuvant (radio-)chemotherapy (NAT). Methods: Seventy PDAC patients with seventy-five arteries showing encasement >180° after completion of NAT were analyzed. All patients underwent surgical exploration with either tumor resection including arterial resection, periadventitial dissection (arterial divestment) or confirmation of locally irresectable disease. CE-CT scans were assessed regarding tumor extent and artery-specific imaging features. The results were analyzed on a per-artery basis. Based on the intraoperative and histopathological findings, encased arteries were classified as either invaded or non-invaded. Results: Eighteen radiologically encased arteries were resected; of these, nine had pathologic evidence for tumor invasion. In 42 encased arteries, the tumor could be removed by arterial divestment. In 13 patients with 15 encased arteries, the tumor was deemed technically irresectable. Median tumor size, length of solid soft tissue contact, and degree of circumferential contiguity by solid soft tissue along the artery in CE-CT were significantly lower in the non-invaded than in the invaded artery group (p ≤ 0.017). Imaging features showed moderate accuracies for prediction of arterial invasion (≤72.0 %). The thresholds ≤26 mm for post-NAT solid soft tissue contact and ≤270° for circumferential contiguity by solid soft tissue had high negative predictive values (≥87.5 %). Conclusion: Although post-NAT prediction of arterial invasion remains difficult, arteries with ≤270° contiguity by soft tissue and arteries with ≤26 mm length of solid soft tissue contact are unlikely to be invaded, with possible implications for surgical planning.